Preventing Criminalization of Default: Legal Certainty in the Settlement of Debt Agreements - Besti Lilyana; Mashuril Anwar; Zulfikar Ali; Shakila Kirana; Dian Herlambang; Dewi Noviyanti (Ius Poenale, 2025)
This research examines the uncertainty in distinguishing fraud and default in debt agreements in Indonesia and its impact on legal certainty. Adopting an empirical normative legal approach, the research analyzes court decisions and relevant legal materials using qualitative methods. It finds that classifying an act as fraud or default depends on whether the agreement is made in bad faith. To enhance legal certainty and prevent the criminalization of good-faith parties, the research proposes several alternatives: establishing guidelines for handling default cases, including compensation for acquitted defendants in court decisions, resolving disputes through simple lawsuits, and utilizing out-of-court settlement mechanisms. The findings provide practical guidance for law enforcement and judicial authorities in differentiating civil defaults from criminal fraud.